Sublethal cytochrome c release generates drug-tolerant persister cells - Kalkavan, Halime; Chen, Mark J.; Crawford, Jeremy C.; Quarato, Giovanni; Fitzgerald, Patrick; Tait, Stephen W.G.; Goding, Colin R.; Green, Douglas R. (Cell, 2022)
Drug-tolerant persister cells (persisters) evade apoptosis upon targeted and conventional cancer therapies and represent a major non-genetic barrier to effective cancer treatment. Here, we show that cells that survive treatment with pro-apoptotic BH3 mimetics display a persister phenotype that includes colonization and metastasis in vivo and increased sensitivity toward ferroptosis by GPX4 inhibition. We found that sublethal mitochondrial outer membrane permeabilization (MOMP) and holocytochrome c release are key requirements for the generation of the persister phenotype. The generation of persisters is independent of apoptosome formation and caspase activation, but instead, cytosolic cytochrome c induces the activation of heme-regulated inhibitor (HRI) kinase and engagement of the integrated stress response (ISR) with the consequent synthesis of ATF4, all of which are required for the persister phenotype. Our results reveal that sublethal cytochrome c release couples sublethal MOMP to caspase-independent initiation of an ATF4-dependent, drug-tolerant persister phenotype.